Cadmium: Mitigation strategies to reduce dietary exposure. Issue 2 (20th January 2020) - Schaefer, Heather R.; Dennis, Sherri; Fitzpatrick, Suzanne
Abstract : Abstract: Cadmium has long been recognized as an environmental contaminant that poses risks to human health. Cadmium is of concern since nearly everyone in the general population is exposed to the metal through the food supply and the ability of the element to accumulate in the body over a lifetime. In support of the United States Food and Drug Administration's (FDA) Toxic Element Working Group's efforts to reduce the risks associated with elements in food, this review sought to identify current or new mitigation efforts that have the potential to reduce exposures of cadmium throughout the food supply chain. Cadmium contamination of foods can occur at various stages, including agronomic production, processing, and consumer preparation for consumption. The presence of cadmium in food is variable and dependent on the geographical location, the bioavailability of cadmium from the soil, crop genetics, agronomic practices used, and postharvest operations. Although there are multiple points in the food supply system for foods to be contaminated and mitigations to be applied, a key step to reducing cadmium in the diet is to reduce or prevent initial uptake by plants consumed as food or feed crops. Due to complex interactions of soil chemistry, plant genetics, and agronomic practices, additional research is needed. Support for field‐based experimentation and testing is needed to inform risk modeling and to develop practical farm‐specific management strategies. This study can also assist the FDA in determining where to focus resources so that research and regulatory efforts can have the greatest impact on reducing cadmium exposures from the food supply. Practical Application: The presence of cadmium in food is highly variable and highly dependent on the geographical location, the bioavailability of cadmium from the soil, crop genetics, and agronomic practices used. This study can assist the FDA in determining where to focus resources so that research and regulatory efforts can have the greatest impact on reducing cadmium exposures from the food supply.